2012
DOI: 10.1177/0363546512453304
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of United States High School Sports-Related Fractures, 2008-09 to 2010-11

Abstract: Background High school athletes sustain millions of injuries annually, many of which are fractures. Fractures can severely affect athletes physically, emotionally, and financially and should be targeted with focused prevention methods. Hypothesis Patterns and primary mechanisms of fractures differ by sport and gender. Study Design Descriptive epidemiology study. Methods High school sports-related injury data were collected from academic years 2008-09 to 2010-11 for 18 sports and from 2009-10 to 2010-11 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 20 publications
3
52
1
Order By: Relevance
“…Although many high school sport-injury epidemiology studies have been conducted, 1,2,[16][17][18] as previously indicated, the results are likely not representative of the sportcamp injury experience. Athlete-exposures are commonly calculated by using athlete-practices or athlete-competitions, 19 with a single practice or competition often held per day.…”
Section: Discussionmentioning
confidence: 88%
“…Although many high school sport-injury epidemiology studies have been conducted, 1,2,[16][17][18] as previously indicated, the results are likely not representative of the sportcamp injury experience. Athlete-exposures are commonly calculated by using athlete-practices or athlete-competitions, 19 with a single practice or competition often held per day.…”
Section: Discussionmentioning
confidence: 88%
“…In the year 2008-2009, hand and finger fractures made up 32.1 % of all fractures sustained by high school athletes in the United States (McCue et al 1979;Swenson et al 2012). In an NFL setting over a 10-year period, metacarpal and finger fractures alone made up over 30 % of injuries to the hand (Palmer and Linscheid 1977;Mall et al 2008).…”
Section: Hand and Finger Fracturesmentioning
confidence: 99%
“…Fractures remain one of the most serious injuries suffered by athletes, resulting in considerable time away from sport, with significant rates of persisting symptoms posttreatment (1)(2)(3)(4)(5). Despite their significant morbidty, there remains considerable variation in their management, due to various factors such as clinician preference and experience, difference in availability of resources and variation in patient desires and expectations (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their significant morbidty, there remains considerable variation in their management, due to various factors such as clinician preference and experience, difference in availability of resources and variation in patient desires and expectations (6,7). Given the significant adverse economic and social implications these injuries can have, both from professional and amateur sport, appropriate knowledge of the optimal management strategies for sport-related fractures is a key factor in modern day sports medicine (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%